KEDUDUKAN HUKUM RELAWAN KEMANUSIAAN BERDASARKAN HUKUM HUMANITER INTERNASIONAL - Nurainun; Anwar Saleh Hasibuan; Rustam (LPPM STISIP Persada Bunda, 2023)
Humanitarian volunteers are an important aspect of the armed conflict between the two countries. Although to help civilians who are in the midst of a humanitarian conflict, a volunteer often has to bet with his soul. This condition is most likely experienced by one or a group of humanitarian volunteers who work in the middle of an area of ??armed conflict for the realization of a sense of humanity and concern for others. This study aims to find out about the position of humanitarian volunteers according to international humanitarian law. Then, the data collection techniques used in this study is an of normative research. The results of the study showed that the protection of humanitarian volunteers is viewed from international humanitarian law that according to the distinction principle in humanitarian law that humanitarian volunteers fall into the category of non-combatants or who are not the object of attack. Protection was provided to humanitarian volunteers in international humanitarian law according to the Geneva Conventions of 1949 and Protocol I, and II because if there is a violation of the Geneva Convention, the crime is an international crime and will be tried in the international criminal court according to the Rome statute of 1998.